Conservation of Nucleosome Positions in Duplicated and Orthologous Gene Pairs - Hiromi Nishida (The Scientific World Journal, 2012)
Although nucleosome positions tend to be conserved in gene promoters, whether they are conserved in duplicated and orthologous genes is unknown. In order to elucidate how nucleosome positions are conserved between duplicated and orthologous gene pairs, I performed 2 comparative studies. First, I compared the nucleosome position profiles of duplicated genes in the filamentous ascomycete Aspergillus fumigatus. After identifying 63 duplicated gene pairs among 9630 protein-encoding genes, I compared the nucleosome position profiles of the paired genes. Although nucleosome positions are conserved more in gene promoters than in gene bodies, their profiles were diverse, suggesting evolutionary changes after gene duplication. Next, I examined the conservation of nucleosome position profiles in 347 A. fumigatus orthologs of S. cerevisiae genes that showed notably high conservation of nucleosome positions between the parent strain and 2 deletion mutants. In only 11 (3.2%) of the 347 gene pairs, the nucleosome position profile was highly conserved (Spearman’s rank correlation coefficient > 0.7). The absence of nucleosome position conservation in promoters of orthologous genes suggests organismal specificity of nucleosome arrangements.